Adult Education and Training Programs for Older Adults in the U.S.Country Comparisons Using PIAAC Data1 - Phyllis A. Cummins; Suzanne R. Kunkel (Adult Education Research Conference, 2015)
The age structure of the U.S. labor force has changed dramatically in recent decades, largely due to the aging of the baby boomer cohort. This shift has increased the importance of gaining a better understanding of how adult education and training influences labor market outcomes for middle-aged and older workers.
Keywords: older adults; adult education and training; labor market outcomes